2023
DOI: 10.3390/infrastructures8020019
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Engineered Slurry-Infiltrated Fibrous Concrete: Experimental and Modelling Approaches

Abstract: Concrete is the central pile for the infrastructure that maintains civilisation and human life. The concrete industry faces many challenges, including improving mechanical properties, eco-friendliness, and durability. In this context, the present study focuses on evaluating and modelling themechanical properties of engineered concrete, namely slurry-infiltrated fibrous concrete (SIFCON). The main experiments will be devoted to measuring and modelling the failures of slabs made from SIFCON under two loading sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Figure 13 illustrates the set-up of the slab specimens mentioned. The pre-defined displacing routine includes about (20)(21)(22) cycles of displacement that are fully reversal. An incremental increase is seen in the peak displacement value until it fails, rising from a (0.25%) drift up to (7%).…”
Section: Cyclic Loading Test Of Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 13 illustrates the set-up of the slab specimens mentioned. The pre-defined displacing routine includes about (20)(21)(22) cycles of displacement that are fully reversal. An incremental increase is seen in the peak displacement value until it fails, rising from a (0.25%) drift up to (7%).…”
Section: Cyclic Loading Test Of Platesmentioning
confidence: 99%
“…It has been found that SIMCON could behave similarly to SIFCON in terms of flexure but with approximately half the fiber volume fracture [17]. In SIFCON, flexural failure occurs in the form of a main crack; meanwhile, multiple cracks were observed in SIMCON [18][19][20]. Other advantages of SIMCON include providing the same strength and energy absorption capacity as SIFCON at a lower fiber volume [21].…”
Section: Introductionmentioning
confidence: 99%
“…Various methodologies and materials have been employed to enhance the durability of slabs under both static and dynamic loading conditions. Tese include shear studs [18], basalt fber-reinforced polymer (FRP) strips [19], hybrid fbers comprising hooked-end steel, polypropylene, and Kevlar [20], high-performance fber-reinforced cementitious composites (HPFRCCs) [21], prestressed concrete [22,23], ferrocement [24], internal anchorage stirrups [25][26][27], Wshaped stirrups [28], truss shear reinforcement [29][30][31], steel plates and slurry-infltrated mat concrete (SIMCON) laminates [32,33], polypropylene fber [33], geogrids [34], and carbon textiles [35]. Increasing the thickness of the slab has demonstrated efcacy in reducing damage and altering failure modes [36], while employing higher-grade concrete has shown some advantages in mitigating slab puncture [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Te research approach includes a detailed comparison through computational simulations, essential for guiding design decisions in particular structural settings. Following the implementation of these reinforcement techniques [32][33][34][35][36][37], there was a noticeable transition in the primary failure mechanism from direct crushing to bending. Additionally, certain strategies have been shown to combine bending with specifc localized crushing efects, as noted in earlier investigations [25][26][27]29].…”
Section: Introductionmentioning
confidence: 99%